Some Remarks on Peculiar Facets of Regulatory Regime Governing Atrocity Crimes in Ethiopia. - Messele, Bereket (Bahir Dar University Journal of Law, 2024)
This piece briefly compares the FDRE Criminal Code provisions on atrocity crimes such as genocide, crimes against humanity, and war crimes with the rules and jurisprudence of International Criminal Law. Unlike the approach followed in the latter, the Criminal Code has expanded the category of protected groups from acts of genocide. It also provides an additional actus reus element. There is no specific atrocity offence called crimes against humanity under the Criminal Code. Ironically, the FDRE Constitution proscribes „crimes against humanity‟ as a generic term that encompasses genocide, war crimes, and other serious offences, instead of being a separate offence. Whilst the Criminal Code lists acts that constitute war crimes, they are not explicitly defined as „grave‟ breaches of the Geneva Conventions in contrast to the Statutes of the ICC, ICTY, and ICTR. Besides, the Criminal Code incorporates other acts as war crimes, the severity of which is questionable in light of the requirements under International Humanitarian Law (IHL). Moreover, unlike the ICC Rome Statute, a plan or policy as part of a large-scale commission of war crimes is not required under the Criminal Code.